Sulprostone-induced reduction of myocardial infarct size in the rabbit by activation of ATP-sensitive potassium channels. - Hide, E. J. (1996)
1. This study examined whether (i) a 1 h pretreatment with or (ii) a continuous infusion of sulprostone reduces myocardial infarct size arising from coronary artery occlusion (60 min) and reperfusion (120 min) in the anaesthetized rabbit. In addition, we investigated whether the observed cardioprotective effect of this selective agonist of prostanoid EP1/EP3 receptors were due to the activation of ATP-sensitive potassium (KATP) channels. 2. In anaesthetized rabbits pretreated with vehicle (5% ethanol in 0.9% saline; 0.05 ml min-1, i.v.) infarct size (expressed as a percentage of the area at risk) after 60 min of coronary artery occlusion followed by 120 min of reperfusion was 59 +/- 4% (n = 10). Pretreatment of rabbits with sulprostone (1.0 microgram kg-1 min-1 for 1 h, discontinued immediately prior to coronary artery occlusion) did not reduce infarct size (60 +/- 4%; n = 4). In contrast, a continuous infusion of sulprostone (1.0 microgram kg-1 min-1) starting 10 min prior to the onset of LAL occlusion and continued throughout the experiment, significantly reduced infarct size (41 +/- 5%, n = 6) when compared to the respective vehicle-treated controls (57 +/- 4%, n = 10; P < 0.05). Sulprostone (pretreatment or continuous infusion) had no effect on any of the haemodynamic parameters measured. 3. The reduction in infarct size afforded by continuous infusion of sulprostone was abolished by pretreatment of rabbits with the KATP channel blocker 5-hydroxydecanoate (5-HD 5 micrograms kg-1; 63 +/- 4%; n = 6). When administered alone, 5-HD had no effect on infarct size when compared to control (52 +/- 6, n = 10). 4. We propose that a continuous infusion of the selective EP1/EP3 prostanoid receptor agonist, sulprostone, reduces infarct size in the anaesthetized rabbit by a mechanism that involves the opening of KATP channels.